PENDIDIKAN AGAMA KRISTEN SEBAGAI UPAYA DALAM MEMBENTUK KARAKTER GENERASI ALPHA - Kordak, Daniel Jufri; Sendow, Mieke Nova (STT Ekklesia Pontianak, 2025)
Abstract: This study examines the role of Christian Religious Education (CRE) in shaping the spiritual character of Generation Alpha, who live amidst the rapid advancement of digital technology and the fast-paced culture driven by social media. These changes present serious challenges to spiritual formation, as faith-based values are often marginalized by pragmatic, instant, and individualistic lifestyles. The purpose of this study is to explain how CRE can serve as a strategic means of developing the spiritual character of Generation Alpha, grounded in a strong faith foundation, equipped with critical thinking skills, and capable of applying Christian values in a relevant way within a changing era. This research employs a descriptive qualitative method with a practical-theological analysis, utilizing literature studies from various theological and Christian educational sources that support the understanding of faith character formation in the digital age. The findings reveal that CRE plays a central role in instilling faith values through contextual approaches, the use of interactive digital media, and the exemplary modeling of teachers and parents. The formation of spiritual character through CRE represents the realization of Christ’s Great Commission in making disciples and nurturing living faith values. This underscores the importance of practical strategies in educating and fostering the spirituality of Generation Alpha. The article highlights the adaptation and innovation of Christian Religious Education (PAK) that are relevant, creative, and contextual for nurturing the spiritual development of today’s digital generation. Abstrak: Penelitian ini mengkaji peran Pendidikan Agama Kristen (PAK) dalam membentuk karakter rohani Generasi Alpha yang hidup di tengah pesatnya perkembangan teknologi digital dan budaya serba cepat yang didorong oleh media sosial. Perubahan ini menimbulkan tantangan serius bagi pembinaan spiritual, karena nilai-nilai iman sering terpinggirkan oleh pola hidup pragmatis, instan, dan individualistis. Tujuan penelitian ini adalah untuk menjelaskan bagaimana PAK dapat berfungsi sebagai sarana strategis dalam membentuk karakter rohani Generasi Alpha yang berakar pada iman yang kokoh, memiliki kemampuan berpikir kritis, serta mampu menerapkan nilai-nilai Kristiani secara relevan di tengah perubahan zaman. Penelitian ini menggunakan metode kualitatif deskriptif dengan analisis praktis-teologis, melalui studi literatur terhadap berbagai sumber teologis dan pendidikan Kristen yang mendukung pemahaman tentang pembentukan karakter iman di era digital. Hasil penelitian menunjukkan bahwa PAK memiliki peran sentral dalam menanamkan nilai-nilai iman melalui pendekatan yang kontekstual, penggunaan media digital yang interaktif, serta keteladanan yang nyata dari guru dan orang tua. Pembentukan karakter rohani melalui PAK merupakan perwujudan Amanat Agung Kristus dalam memuridkan dan menanamkan nilai-nilai iman yang hidup. Hal ini menegaskan pentingnya strategi praktisi dalam mendidik serta menumbuhkan spiritualitas Generasi Alpha. Artikel ini menyoroti adaptasi dan inovasi PAK yang relevan, kreatif, dan kontekstual bagi pembinaan spiritual generasi digital masa kini.